Turkish reference ranges for the left fetal modified myocardial performance index - Yakut, Kadriye; Öcal, Doğa Fatma; Öztürk, Filiz; Öztürk, Merve; Sanhal, Cem Yaşar; Çelen, Şevki; Üstün, Yaprak (The Turkish Journal of Pediatrics, 2021)
Background. This study aimed to assess fetal cardiac left ventricular function in healthy pregnant women by calculating the modified myocardial performance index (Mod-MPI) and to construct reference ranges for the Turkish population. Methods. One-hundred-two randomly selected healthy singleton pregnant women ranging between 25 and 39 gestational weeks were included in the study. Left fetal Mod-MPI was measured for each pregnant woman. Women with chronic systemic diseases or fetuses with chromosomal or structural abnormalities were excluded from the study. Mitral valve (MV) and aortic valve (AoV) clicks were used as landmarks to define the following time periods that were used to calculate the Mod-MPI: isovolumetric contraction time (ICT), isovolumetric relaxation time (IRT), and ejection time (ET). Results. The mean Mod-MPI was 0.42±0.10. The mean IRT, ICT, and ET were 43.5±10.2, 27.27±8.1, and 170.5±16.9, respectively. A significant correlation was found between Mod-MPI and gestational age, umbilical artery systolic/diastolic (UA S/D) ratio and the middle cerebral artery pulsatility index (MCA PI) values (r=0.199, p=0.047, r=-0.328, p=0.001, and r=-0.0349, p=0.001, respectively) Conclusions. The current study`s results will be a reference for future studies, especially studies investigating pathological conditions that impact fetal cardiac function.